The Effect of Transfer Pricing, Capital Intensity, and Leverage on Tax Avoidance with Company Size as a Moderating Variable - Tamam, Badrud; Tarmidi, Deden (LifeSciFi, 2025)
The complexity of business transactions in Indonesia’s mining sector has raised concerns about tax avoidance, which reduces state revenue through legal loopholes. This study aims to analyze the impact of transfer pricing, capital intensity, and leverage on tax avoidance, with company size as a moderating variable, in mining companies listed on the Indonesia Stock Exchange from 2019 to 2023. The research employs a quantitative approach using panel data regression with data from 16 companies, resulting in 80 observations. Tax avoidance is measured by the ratio of tax expenses to pre-tax profits, transfer pricing by related party transactions to total sales, capital intensity by fixed assets to total assets, leverage by total debt to total assets, and company size by the natural logarithm of total assets. The findings indicate that transfer pricing and leverage significantly influence tax avoidance, while capital intensity and company size as a moderating variable do not. These results suggest that mining companies use profit shifting and debt financing to minimize tax obligations. This study contributes to understanding tax avoidance practices and offers recommendations for policymakers to enhance regulations, particularly on transfer pricing and debt-related deductions, to ensure fairer tax contributions in the mining sector.